1992
DOI: 10.1071/rj9920065
|View full text |Cite
|
Sign up to set email alerts
|

The conservation status of birds in arid Australia.

Abstract: The impression has been given in previous studies that there are few bird conservation problems in the arid zone, particularly because not one of a total of 230 species has become extinct. In stark contrast, almost half of the native terrestrial mammalian fauna of the Australian arid zone has become extinct on the mainland since European occupation. Here we show that the status of one half of the avifauna has changed since European occupation, and conclude there are many threats to avian biodiversity at the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
4
52
2
Order By: Relevance
“…There is substantial evidence that the recruitment of many long-lived perennial tree species by seed or vegetative suckers is inhibited under grazing pressure (Lange and Graham 1983;Auld 1995). It has long been suggested that in Australia the major cause of reduced regeneration of perennial trees and grasses were rabbits, goats (Lange and Graham 1983) and domestic stock (Auld 1995), particularly in riverine communities (Reid and Fleming 1992). However, anecdotal evidence collected throughout this study suggests that Eucalyptus species in riverine communities regenerate well in comparison to some residual communities.…”
Section: Impacts Of Grazingcontrasting
confidence: 39%
“…There is substantial evidence that the recruitment of many long-lived perennial tree species by seed or vegetative suckers is inhibited under grazing pressure (Lange and Graham 1983;Auld 1995). It has long been suggested that in Australia the major cause of reduced regeneration of perennial trees and grasses were rabbits, goats (Lange and Graham 1983) and domestic stock (Auld 1995), particularly in riverine communities (Reid and Fleming 1992). However, anecdotal evidence collected throughout this study suggests that Eucalyptus species in riverine communities regenerate well in comparison to some residual communities.…”
Section: Impacts Of Grazingcontrasting
confidence: 39%
“…Nomads instead can be highly habitat specific, keying into specific environmental conditions such as vegetation seeding and flowering events (Ziembicki & Woinarski 2007;Pavey & Nano 2013;Tischler et al 2013;Webb et al 2014), making them less resilient to environmental change than generalist sedentary species. There has been widespread modification and transformation of vegetation across inland Australia, with 46% of the continent subject to grazing of native vegetation (SoE 2011), and this is likely to have impacted nomadic birds (Reid & Fleming 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Movement itself could be risky in the sense that locations and timings of suitable resources are unpredictable and irregular (MacNally 2009). Additionally, in some cases, threats can be concentrated into precisely the areas to which nomadic species contract ; for example, both invasive predators and livestock grazing follow rainfall patterns during prolonged drought (Reid & Fleming 1992;Grenville et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations